A sensitive LC assay for the simultaneous determination of centbutindole and its metabolite in rat serum using fluorescence detection - Issar M.; Singh S.K.; Mishra B.; Gupta R.C. (My University, 2025)
Centbutindole (±) 2-γ-[(p-fluorobenzoyl)propyl]-1, 2, 3, 4, 6, 7, 12, 12a-octahydro-pyrazino (2′, 1′: 6, 1) pyrido [3, 4-b] indole (I), is a new neuroleptic agent developed by Central Drug Research Institute, India. In the present study, a high performance liquid chromatography (HPLC) assay method for the simultaneous assay for I and its metabolite (II) in rat serum was developed and validated. The present method requires only 1 ml of serum with detection levels similar to that reported earlier using 4 ml serum. This assay has been found to be more suited for pre-clinical as well as phase IV studies. Linearity was observed between 1.25 and 40 ng/ml for I and 0.625 and 20 ng/ml for II in rat serum. Recoveries were consistent for both the analytes over the concentration ranges studied. Variation in intra-and inter-batch accuracy and precision were within acceptable limits of ±20% at lowest limit of quantitation, whereas at higher concentrations it was ±15%. The assay method was employed for the study of the pharmacokinetics and metabolism of I in rats. The parent compound and its metabolites were quantitated in serum and could be monitored up to 24 h post dose. © 2002 Elsevier Science B.V. All rights reserved.